KONSEP EKONOMI PENDIDIKAN DALAM PENGELOLAAN SUMBER DAYA MADRASAH - Azkiyah, Nur Atik; Nurochim, Nurochim; Ratnaningsih, Sita; Sari, Novita Dwi Indah; Rifanti, Nina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the implementation of the concept of educational economics in resource management at MAM 02 Pondok Modern. Educational economics is seen as a strategic approach that emphasizes the importance of efficiency and effectiveness in the use of educational resources, especially in institutions that face budget constraints. The research uses a descriptive qualitative method with data collection techniques through interviews and field observations, which are then analyzed using the process of reduction, categorization, and triangulation of data. The results of the study show that MAM 02 Pondok Modern has applied the principles of education economics through needs-based budget planning, optimization of the use of facilities and infrastructure, and the use of digital technology to improve administrative efficiency. However, madrasas still face obstacles in the form of limited financing and human resource management capabilities. These findings indicate that the efficiency of education is not only influenced by the amount of budget inputs, but also the quality of management in optimizing available resources. This research emphasizes the importance of increasing managerial capacity and funding innovation as a strategy to strengthen the implementation of the education economy in madrasas, in order to support the continuous improvement of the quality of learning. ABSTRAK Penelitian ini bertujuan menganalisis implementasi konsep ekonomi pendidikan dalam pengelolaan sumber daya di MAM 02 Pondok Modern. Ekonomi pendidikan dipandang sebagai pendekatan strategis yang menekankan pentingnya efisiensi dan efektivitas dalam penggunaan sumber daya pendidikan, terutama pada lembaga yang menghadapi keterbatasan anggaran. Penelitian menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara dan observasi lapangan, yang kemudian dianalisis menggunakan proses reduksi, kategorisasi, serta triangulasi data. Hasil penelitian menunjukkan bahwa MAM 02 Pondok Modern telah menerapkan prinsip ekonomi pendidikan melalui perencanaan anggaran berbasis kebutuhan, optimalisasi pemanfaatan sarana dan prasarana, dan penggunaan teknologi digital untuk meningkatkan efisiensi administrasi. Meskipun demikian, madrasah masih menghadapi kendala berupa keterbatasan pembiayaan dan kemampuan pengelolaan sumber daya manusia. Temuan ini mengindikasikan bahwa efisiensi pendidikan tidak hanya dipengaruhi oleh besarnya input anggaran, tetapi juga kualitas manajemen dalam mengoptimalkan sumber daya yang tersedia. Penelitian ini menegaskan pentingnya peningkatan kapasitas manajerial dan inovasi pendanaan sebagai strategi penguatan implementasi ekonomi pendidikan di madrasah, guna mendukung peningkatan mutu pembelajaran secara berkelanjutan.